2021
DOI: 10.1038/s41598-021-93575-0
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation does not affect hypertension or the renin-angiotensin system in a rodent model of juvenile-onset polycystic kidney disease: clinical implications

Abstract: We examined the effect of total and afferent renal denervation (RDN) on hypertension and the renin-angiotensin system (RAS) in a rodent model of juvenile-onset polycystic kidney disease (PKD). Lewis Polycystic Kidney (LPK) and control rats received total, afferent or sham RDN by periaxonal application of phenol, capsaicin or normal saline, respectively, and were monitored for 4-weeks. Afferent RDN did not affect systolic blood pressure (SBP) determined by radiotelemetry in either strain (n = 19) while total RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…However, such morphological evidence of sympathetic regrowth was not accompanied by recovery in renal NE content [ 23 ]. Another recent study showed anatomical evidence of renal sympathetic and sensory nerve regrowth 4 weeks post procedure in hypertensive rats, but with sustained BP reduction relative to sham animals [ 16 ]. Likewise, both anatomical and functional re-innervation were demonstrated 11 months after RF RDN in normotensive sheep via histological staining and response to stimulation, respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, such morphological evidence of sympathetic regrowth was not accompanied by recovery in renal NE content [ 23 ]. Another recent study showed anatomical evidence of renal sympathetic and sensory nerve regrowth 4 weeks post procedure in hypertensive rats, but with sustained BP reduction relative to sham animals [ 16 ]. Likewise, both anatomical and functional re-innervation were demonstrated 11 months after RF RDN in normotensive sheep via histological staining and response to stimulation, respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“… 99 Benefits in blood pressure reduction and/or renal protection after renal denervation were also observed in the uninephrectomised SHR model, 100 the fetal uninephrectomised CKD sheep model, 101 the CKD rabbit model induced by glomerular layer lesioning and uninephrectomy, 102 uninephrectomised rats fed with high salt diet 103 and the Han: SPRD-Cy/+ model of autosomal dominant polycystic kidney disease, 104 though no response, either blood pressure or renoprotective, was seen in the Lewis polycystic kidney disease (LPK) rat model, which resembles autosomal recessive polycystic kidney disease. 75 In this case, the CKD model arose from an early onset genetic cause, and the degree of hypertension and renal dysfunction was marked from an early age. 75 From a translational perspective, the application of RDN in patients such as those with childhood onset genetic kidney disease should be carefully considered to avoid unnecessary procedures.…”
Section: Introductionmentioning
confidence: 95%
“… 75 In this case, the CKD model arose from an early onset genetic cause, and the degree of hypertension and renal dysfunction was marked from an early age. 75 From a translational perspective, the application of RDN in patients such as those with childhood onset genetic kidney disease should be carefully considered to avoid unnecessary procedures. A lack of renoprotective effect of RDN was also reported in a porcine chronic renal insufficiency model induced by selective renal artery embolisation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pressure-dependent feedback in juxtaglomerular renin secretion is the cause of renin reduction. However, the mechanism causing the decrease in intrarenal RAS is not clearly identified [ 95 ]. Renal denervation does not impact hypertension or RAS, which may be because other pathways involved in controlling intrarenal RAS, such as the prorenin receptor, nuclear receptors, and prostaglandins, offset RDN effect.…”
Section: Introductionmentioning
confidence: 99%